Nationwide Smoking Cessation Treatment Support Program – Turkey project. Issue 1 (January 2015) - Çelik, İsmail; Yüce, Deniz; Hayran, Mutlu; Erman, Mustafa; Kılıçkap, Saadettin; Buzgan, Turan; Irmak, Hasan; Tosun, Nihat; Tuncer, Murat; Akdağ, Recep
Highlights In 2011, Turkish MoH initiated a nation-wide "Smoking Cessation Treatment Support Program" (SCTSP). Major interventions were free medication (Varenicline and Bupropion) and primary care support. 164, 733 participants were recruited in designated smoking cessation clinics. The real-life quit rates were comparable to those of clinical evidence to date. This success model could be implemented to the public health policy of other countries.